Paraspinous Sagittal Shift (PSSS): a novel approach for transmuscular quadratus lumborum block for hip surgery analgesia - four cases report - Alabd,Ahmad S. (2020)
Abstract Background: Effective pain management is essential for successful rehabilitation and enhanced recovery after joint arthroplasty. The Quadratus Lumborum Block (QLB) has mostly been described for abdominal surgery, but has also recently been applied to hip surgery patients. Methods: In the following cases series, we suggest a modification of the TQL block described as Paraspinous Sagittal Shift QL block. We hypothesize that this approach may allow better LA spread to the lumbar nerve roots. Such technique involves a craniocaudal approach of LA injection between the QL and PM muscles behind the Anterior Thoracolumbar Fascia (ATLF) at the level of L4. Cases were provided with combined GA and PSSS modification of QL block via a single shot or catheter technique. Results: Sensory distribution of the block in the four patients studied was found to cover the area between the T11-12 and L4-5 dermatomes. Spread of the injectate was confirmed via an A-P fluoroscopy imaging of the lumbosacral spine after injection of a mixture of LA and a contrast in the plane between the QL and PM muscles in two cases. Conclusions: The PSSS technique for TQL block may be beneficial as a part of multimodal analgesia for hip surgeries. This technique may be a safe alternative to psoas compartment block; however, future comparative studies are recommended. The PSSS technique for TQL block also may provide an easy access for catheter insertion.